Use of lip sync in the Spanish dubbing of the short film "The butterfly Circus” - Lora Vera, Fátima (2018)
This research named “Use of the lip sync in the Spanish dubbing of the short film ‘The Butterfly Circus’, Chiclayo – 2017”. It’s a descriptive research based on the cinematographic approach which confirms that the specialized language used in this industry is not only linguistically codified, but it also includes codes that contribute to give the final message. The former consists of linguistic, paralinguistic, musical, special effects and sound arrangement codes, whereas visual codes include iconographic, photographic, graphic, planning, syntactic or montage, and mobility codes. For this research the analytical synthetic method was applied to evaluate the lip sync in the Spanish dubbing of the short film ‘The Butterfly Circus’ through the development of a checklist and an analysis matrix. The population was composed of the content of the short film and the sample was the script divided by takes.  KEY WORDS: LIP SYNC, DUBBING, TAKES